2021
DOI: 10.3390/microorganisms9081704
|View full text |Cite
|
Sign up to set email alerts
|

The Sisal Virome: Uncovering the Viral Diversity of Agave Varieties Reveals New and Organ-Specific Viruses

Abstract: Sisal is a common name for different plant varieties in the genus Agave (especially Agave sisalana) used for high-quality natural leaf fiber extraction. Despite the economic value of these plants, we still lack information about the diversity of viruses (virome) in non-tequilana species from the genus Agave. In this work, by associating RNA and DNA deep sequencing we were able to identify 25 putative viral species infecting A. sisalana, A. fourcroydes, and Agave hybrid 11648, including one strain of Cowpea Mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 94 publications
0
16
0
Order By: Relevance
“…However, we also detected three contigs related to Barley stripe mosaic virus (BSMV) and it will not be discussed in this study. A BLASTx search revealed that one contig (3479 nt) shared 52.62% amino acid pairwise identity with Sisal-associated virgavirus A (a virus found in Agave sisalana that belongs to unclassi ed Virgaviridae)[6], while the other contig (3436 nt) shared 48.63% amino acid pairwise identity with Sisal-associated virgavirus C [11]. Moreover, we found that the contigs displayed no signi cant similarity using BLASTn.…”
Section: Provenance Of the Virus Materialsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, we also detected three contigs related to Barley stripe mosaic virus (BSMV) and it will not be discussed in this study. A BLASTx search revealed that one contig (3479 nt) shared 52.62% amino acid pairwise identity with Sisal-associated virgavirus A (a virus found in Agave sisalana that belongs to unclassi ed Virgaviridae)[6], while the other contig (3436 nt) shared 48.63% amino acid pairwise identity with Sisal-associated virgavirus C [11]. Moreover, we found that the contigs displayed no signi cant similarity using BLASTn.…”
Section: Provenance Of the Virus Materialsmentioning
confidence: 95%
“…According to the 2020 International Committee on Taxonomy of Viruses (ICTV) taxonomy (https://talk.ictvonline.org/ictv-reports/ictv_online_report/positive-sense-rnaviruses/w/virgaviridae), the family includes the genera Furovirus, Hordeivirus, Goravirus, Pecluvirus, Pomovirus, Tobamovirus, and Tobravirus. In recent years, many viruses belonging to the Virgaviridae family but different from any of the known genera in this family have been characterized in different hosts [10][11][12]. Therefore, those viruses were temporarily assigned to unclassi ed Virgaviridae.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing NT and NR databases, as well as Pfam and Swissprot databases, two assembled contigs were found to be homologous to viral RNA-directed RNA-polymerase. A BLASTx search against the two selected contigs revealed that one contig (3479 nt) shared 52.62% amino acid pairwise identity with Sisal-associated virgavirus A (a virus found in Agave sisalana that belongs to unclassi ed Virgaviridae)[6], while the other contig (3436 nt) shared 48.63% amino acid pairwise identity with Sisal-associated virgavirus C [11]. Moreover, we found that the contigs displayed no signi cant similarity using BLASTn.…”
Section: Provenance Of the Virus Materialsmentioning
confidence: 99%
“…According to the 2020 International Committee on Taxonomy of Viruses (ICTV) taxonomy (http:// ictv.global/report), the family includes the genera Furovirus, Hordeivirus, Goravirus, Pecluvirus, Pomovirus, Tobamovirus, and Tobravirus. In recent years, many viruses belonging to the Virgaviridae family but different from any of the known genera in this family have been characterized in different hosts [10][11][12]. Therefore, those viruses were temporarily assigned to unclassi ed Virgaviridae.…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2020 International Committee on Taxonomy of Viruses (ICTV) taxonomy (https://talk.ictvonline.org/ictv-reports/ictv_online_report/positive-sense-rnaviruses/w/virgaviridae), this virus family contains seven genera such as Furovirus, Hordeivirus, Goravirus, Pecluvirus, Pomovirus, Tobamovirus, and Tobravirus. However, in recent years many new viruses which couldn't be recognized belonging to any above known genera in the Virgaviridae family have been discovered in many different plant hosts [10][11][12] and these new viruses were therefore assigned as unclassi ed Virgaviridae.…”
Section: Introductionmentioning
confidence: 99%